2016
DOI: 10.1038/tpj.2015.92
|View full text |Cite
|
Sign up to set email alerts
|

A genetic factor associated with low final bone mineral density in children after a long-term glucocorticoids treatment

Abstract: Treatment with glucocorticoids is associated with lower bone mineral density (BMD). We performed a genome-wide association study to analyze interactive effects between genotypes and cumulative dose of prednisone (PD) over 4.3 years of follow-up period on the final BMD Z-scores in 461 white children from the Childhood Asthma Management Program. No variants met the conventional criteria for genome-wide significance, and thus we looked for evidence of replication. The top 100-ranked single nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…FSK stimulates glucocorticoid production in the adrenal cortex by increasing cAMP (34), and glucocorticoids could negatively regulate osteoblast proliferation and differentiation (35). A bone mass decrease was found in children after long-term glucocorticoid treatment (36). Therefore, FSK may have had only limited effects on the body length and bone mass phenotype in Gpr126 deletion mice due to microenvironmental factors including IL-6 expression induced by FSK, offsetting the positive effect of FSK on osteoblasts in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…FSK stimulates glucocorticoid production in the adrenal cortex by increasing cAMP (34), and glucocorticoids could negatively regulate osteoblast proliferation and differentiation (35). A bone mass decrease was found in children after long-term glucocorticoid treatment (36). Therefore, FSK may have had only limited effects on the body length and bone mass phenotype in Gpr126 deletion mice due to microenvironmental factors including IL-6 expression induced by FSK, offsetting the positive effect of FSK on osteoblasts in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene studies have identified several single‐nucleotide polymorphisms (SNPs) associated with low BMD in patients with ALL, including those in the vitamin D receptor ( VDR ) 5′‐end ( Cdx‐2/GATA polymorphism) haplotype 3 ( P = .01), the genes encoding methylenetetrahydrofolate reductase (the MTHFR 677 thymine [T] allele) and methionine synthase reductase (the MTRR 66 guanine [G] allele; P ≤ .01 with 2 or more risk alleles), CRHR1 (the G allele of reference SNP rs1876828; P = .02 for boys), and RAPGEF5 (the T allele of rs6461639; P = .016) . However, there has been no genome‐wide analysis of low BMD in patients with ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate gene studies have identified several single-nucleotide polymorphisms (SNPs) associated with low BMD in patients with ALL, including those in the vitamin D receptor (VDR) 5 0 -end (Cdx-2/GATA polymorphism) haplotype 3 (P 5 .01), 8 the genes encoding methylenetetrahydrofolate reductase (the MTHFR 677 thymine [T] allele) and methionine synthase reductase (the MTRR 66 guanine [G] allele; P .01 with 2 or more risk alleles), 9 CRHR1 (the G allele of reference SNP rs1876828; P 5 .02 for boys), 10 and RAPGEF5 (the T allele of rs6461639; P 5 .016). 11 However, there has been no genome-wide analysis of low BMD in patients with ALL. Therefore, we evaluated clinical, pharmacokinetic, and genetic risk factors influencing BMD, especially those associated with a decline in BMD Z-scores during therapy, in children with ALL who received treatment on a contemporary protocol without cranial irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…There were 1409 results after removal of duplicates generated from the search strategy, but of these, only five were eligible for inclusion [29][30][31]. From the survey sent, two additional studies were discovered [32,33] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…One study examined ADRs with inhaled short acting beta-2 agonists (SABA) [29], one analysed long acting beta-2 agonists (LABA) [30], three studies examined the use of corticosteroids [31][32][33], while no studies have examined ADRs occurring with either leukotriene receptor antagonists (LTA) or theophylline. For the SABA and LABA studies, a candidate gene approach was applied [29,30], whereas in the three corticosteroid studies, genome-wide association studies (GWAS) were used [31][32][33].…”
Section: Resultsmentioning
confidence: 99%